CONSTRAINING UPPER-MANTLE ANELASTICITY USING SURFACE-WAVE AMPLITUDE ANOMALIES - Durek, J; Ritzwoller, M; Woodhouse, J (1993)
The paper presents an iterative method to constrain lateral variations in surface wave attenuation using long-period surface wave amplitude anomalies. The method acts to isolate the anelastic signal from elastic focusing effects, yielding largely unbiased estimates of lateral variations in the inverse seismic quality factor, q(ω)=Q-1(ω), of the surface wave. In the zeroth iteration, linearized ray theory motivates the construction of a reduced datum, using measurements from four consecutive surface wave orbits, which is insensitive to elastic heterogeneity, an operation which require no a priori knowledge of elastic structure. -from Authors